2020
DOI: 10.1039/c9ra10135g
|View full text |Cite
|
Sign up to set email alerts
|

Nisin/polyanion layer-by-layer films exhibiting different mechanisms in antimicrobial efficacy

Abstract: Polyanion–nisin multilayer films exhibit antimicrobial activity by controlled release of nisin or as stable biofilm inhibiting coatings depending on polyanion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…The presence of amorphous drug in zein fibers, and the high encapsulation efficiency, prolonged stability of the drug within the fibers, and its near-complete release from the fibers, demonstrates that the fabricated zein fibers may potentially be used as a fast release antimicrobial layer, that could be introduced into wound dressings to reach initial MIC. The fast release of antimicrobial agents is beneficial in heavily contaminated wounds, for eradicating existing bacteria and reducing the formation of a biofilm [67][68][69]. Successful optimization of the physico-mechanical properties of zein fibers, such as higher hydrophilicity, elasticity and better water stability, as compared to pure zein fibers, brings them closer to realizing the properties of an ideal wound dressing.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of amorphous drug in zein fibers, and the high encapsulation efficiency, prolonged stability of the drug within the fibers, and its near-complete release from the fibers, demonstrates that the fabricated zein fibers may potentially be used as a fast release antimicrobial layer, that could be introduced into wound dressings to reach initial MIC. The fast release of antimicrobial agents is beneficial in heavily contaminated wounds, for eradicating existing bacteria and reducing the formation of a biofilm [67][68][69]. Successful optimization of the physico-mechanical properties of zein fibers, such as higher hydrophilicity, elasticity and better water stability, as compared to pure zein fibers, brings them closer to realizing the properties of an ideal wound dressing.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated the capacity of nisin to inhibit the microbial growth of gram positive bacteria, including the highly pathogenic bacteria found in food, such as Staphylococcus aureus (Godoy- Santos et al, 2019), Staphylococcus epidermidis (Fael & Demirel, 2020), Clostridium botulinum (Gharsallaoui et al, 2016), and L. monocytogenes (Bastarrachea et al, 2010), among other pathogenic microorganisms (Nakazato et al, 2017).…”
Section: Effects Of Treatments On L Monocytogenes E Coli and S Typhimurium Cell Countsmentioning
confidence: 99%
“…Nisin has also been formulated as films released from polymer/nisin multilayers; whereas nisin/polyacrylic acid (PAA) layers disintegrated in 24 h in water solution, nisin/dextran sulfate (DX) films were stable for 14 days without releasing nisin; both films hampered the spread of Staphylococcus epidermidis biofilms in disk diffusion tests; therapeutic utility proposed for nisin/PAA films was treating burns and wounds due to the quick nisin release, whereas nisin/DX coatings would impart steady sterilization of surfaces over long periods of time [ 71 ].…”
Section: Asa With Ampsmentioning
confidence: 99%